The Receipt of Grants as a Key Determinant of Venture Investment Size in Russia-based IT Startups - Ivan Rodionov; Alexander Semenov; Aleksey Oskin (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2020)
Since 2006, Russian policymakers have been actively taking various measures to stimulate the venture capital market. Government venture capital funds are being created, for example, the Russian Venture Company with a capital of 15 billion rubles. Since 2011, thanks to the new legal mechanism, state-owned companies begin to invest in private venture funds. These measures have led to increased fundraising for startups. The main mechanism of such financing is grant support for young companies. According to 2018, the amount of grants to the total amount of funds raised in Russia is one of the highest among developed and developing countries, for comparison in the USA, it is more than 2.5 times lower. The venture market specifics is such that when deciding whether to invest in a company, investors inevitably turn their attention to the previous rounds of financing the company. The purpose of the work is to analyze the effect of the money grant received on the volumes of attracting subsequent financing.To analyze the impact of the receiving money grant, the determinant approach was used, as the most common in research on this topic. Based on a sample of 184 Russian IT startups, two OLS models have built to show the effect of money grant size to follow-on investment rounds.As a result, various sets of determinants were considered that explain the volume of investments attracted by startups for both international markets and the Russian market. In addition, an excursus was conducted to study the effectiveness of government venture funds, which are the main grantors in the Russian venture market. Based on the results of previous studies on this topic, it was shown that the size of the money grant has a positive effect on the amount of funding attracted in both follow-on rounds. For comparison, a number of previous studies of the Russian venture capital market show that the investment size of the current round has influenced only by the previous fundraising. Such a result testifies to the attractiveness for investors Russian IT startups that received grant support.The scientific novelty of the article is that the amount of funding attracted by startups is explained by such a specific indicator as grant support. In addition, the results obtained have certain practical value for those who invest in Russian startups. Investing in startups that received grants increases the likelihood of an exit for the investor in the next investment round.